Bahasa atau Komunikasi: Mengkritisi "Metode-Penelitian Bahasa" - Herudjati Purwoko (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
This paper questions critically the public notion of most researchers in linguistics and other Social-sciences on the conventional viewpoint on natural language. Then, it tries to forward a revisited viewpoint in the hope that those researchers who are interested in dealing with the transcripts of natural langunge will regard them as valuable data for their research projects. The paper also encourages the social scientists to pay serious attention to linguistic transcripts and utilize them as value data due to the rich socio-cultural contents.